2015
DOI: 10.36510/learnland.v8i2.710
|View full text |Cite
|
Sign up to set email alerts
|

Twitter in a Bachelor of Education Course: Student Experiences

Abstract: The purpose of this article is to describe student experiences when incorporating Twitter into a Bachelor of Education (BEd) course. Data for this participatory action research were gathered from eight first-year BEd students who provided written answers to 16 open-ended questions and participated in two focus group interviews. Findings indicated that, after participants completed a Twitter assignment, their views of Twitter and its applicability in educational realms changed. Analyzed through the emerging con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…For the 2017-18 academic year the subject's teaching team will implement exclusively a continuous assessment system based on learning through activities; that is, students will be offered only Option A, since it is considered more effective from the learning point of view. They will continue to be offered different kinds of activities, but all of them will involve participation on Twitter in their final phase, as this is considered a motivational environment that can reinforce students' academic commitment, as Jones and Baltzersen (2017) assert, informal and/or formal communication, as recent research (Dabbagh & Kitsantas, 2011;Tang & Hew, 2017) has found, and interaction between faculty and students, as Preston et al (2015) found. The activity will be designed on the basis of the "push" technology described by Tang and Hew (2017), the teacher initiating communication by sending questions and discussion topics that encourage the process of reflection and debate through the Twitter network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 2017-18 academic year the subject's teaching team will implement exclusively a continuous assessment system based on learning through activities; that is, students will be offered only Option A, since it is considered more effective from the learning point of view. They will continue to be offered different kinds of activities, but all of them will involve participation on Twitter in their final phase, as this is considered a motivational environment that can reinforce students' academic commitment, as Jones and Baltzersen (2017) assert, informal and/or formal communication, as recent research (Dabbagh & Kitsantas, 2011;Tang & Hew, 2017) has found, and interaction between faculty and students, as Preston et al (2015) found. The activity will be designed on the basis of the "push" technology described by Tang and Hew (2017), the teacher initiating communication by sending questions and discussion topics that encourage the process of reflection and debate through the Twitter network.…”
Section: Discussionmentioning
confidence: 99%
“…The processes of social interaction and the patterns of exchanging information that can be developed using Twitter have a positive influence in the sense of generating a community amongst the students (Bligh et al, 2017). In addition, there is no shortage of research that emphasises the value of Twitter as a space that reinforces the interaction between teachers and students (Preston, Jakubiec, Jones, & Earl, 2015). Carpenter and Krutka (2015) say that teachers like Twitter for the opportunities it opens up for professional development, its immediacy, its interactive potential and usability.…”
Section: Introductionmentioning
confidence: 99%
“…For Kent and Carolyn, the flipped classroom was about releasing their dominance in front of the class and embracing a collaborative student-centered community of synergetic, symbiotic classroom learners. The 21st century teacher-student dynamic reinforces learning to be decentralized, non-hierarchical, social, hyperlinked, collaborative, and synergetic (Preston, Jakubiec, Jones, & Earl, 2015), and it encourages students to be knowledge activators, producers, and disseminators (Fullan, 2013(Fullan, , 2014Prensky, 2012;November, 2010November, , 2012. Twenty-first century learning calls for each student to be a tutor, coach, and instructor for his/her classmates, and, at times, the student needs to be a teacher of their teacher (especially in the dynamics of action research).…”
Section: Summary and Discussion Of Resultsmentioning
confidence: 99%
“…A number of studies discuss the merits of SM for collaboration between students (Carpenter, 2014;Dymoke & Hughes, 2009;Preston, Jakubiec, Jones, & Earl, 2015;Wheeler, 2009;Wheeler & Wheeler, 2009), with some feedback showing that participants valued the ease of collaboration not tied to a physical space and time (Preston et al, 2015). Online collaboration appears particularly effective when used as a way of bringing geographically distant individuals together (Winzenried, 2012).…”
Section: Pedagogical Principlesmentioning
confidence: 99%